[Afisz. Incipit] Zarządzenie na zasadzie art. 16 ustawy z dnia 9.IV.1938 r. ... / Jan Kapusta. - Kapusta, Jan (1908-1953) ([wydawca nieznany], 1948)
Afisz informujący o rejestracji mężczyzn z rocznika 1931.